2011
DOI: 10.1089/neu.2011.1842
|View full text |Cite|
|
Sign up to set email alerts
|

Modulation of Ischemia-Induced NMDAR1 Activation by Environmental Enrichment Decreases Oxidative Damage

Abstract: In this study, we examined whether enriched environment (EE) housing has direct neuroprotective effects on oxidative damage following transient global cerebral ischemia. Fifty-two adult male Wistar rats were included in the study and received either ischemia or sham surgery. Once fully awake, rats in each group were randomly assigned to either: EE housing or socially paired housing (CON). Animals remained in their assigned environment for 7 days, and then were killed. Our data showed that glutamate receptor ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 48 publications
3
31
0
Order By: Relevance
“…Our data show the temporal pattern of IGF-1 expression and signaling immediately after CMF treatment and later during the recovery period. The upregulation of IGF-1 levels and activation of the Akt and Erk1/2 pathways immediately after CMF therapy suggest a neuroprotective role aimed at maintaining normal brain function following a relatively stressful event, since there is increasing evidence that chemotherapy can induce both direct and indirect neurotoxicity [11, 16, 17, 32]. The neuroprotective role of IGF-1 is underscored in our results showing that exogenous administration after CMF therapy was able to decrease the number of apoptotic cells and increase the survival of NPCs that proliferate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data show the temporal pattern of IGF-1 expression and signaling immediately after CMF treatment and later during the recovery period. The upregulation of IGF-1 levels and activation of the Akt and Erk1/2 pathways immediately after CMF therapy suggest a neuroprotective role aimed at maintaining normal brain function following a relatively stressful event, since there is increasing evidence that chemotherapy can induce both direct and indirect neurotoxicity [11, 16, 17, 32]. The neuroprotective role of IGF-1 is underscored in our results showing that exogenous administration after CMF therapy was able to decrease the number of apoptotic cells and increase the survival of NPCs that proliferate.…”
Section: Discussionmentioning
confidence: 99%
“…Equal amounts of protein (40 μg) from each rat were loaded and separated by SDS-PAGE gel electrophoresis as previously described [17]. The nitrocellulose membranes containing the protein bands were stained with 0.5% Ponceau Red to visualize protein loading, then destained and non-specific binding sites were blocked by incubation of the membranes in 5% powdered milk in Tris-buffered saline containing 0.5 ml/L Tween-20.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting studies have suggested that exposure to EE treatment after brain injury leads to neuroprotective effects in animal models [9, 10]. Recently, EE treatment has been translated into a rehabilitation strategy for poststroke patients in the clinical setting [11].…”
Section: Introductionmentioning
confidence: 99%
“…27 Interestingly, a recent study of adult rats showed that an enriched environment has a protective effect on glutamate excitotoxicity, reducing oxidative damage. 28 In contrast, an impoverished environment has a negative impact on neural plasticity. For instance, rats that live in a traditional laboratory cage develop hippocampal atrophy.…”
mentioning
confidence: 99%